The absence of fans removes the home advantage associated with penalties called by National Hockey League referees - Guérette, J.; Blais, C.; Fiset, D. (PLOS ONE, 2021)
The COVID-19 pandemic has had a major impact on professional sports, notably, forcing the National Hockey League to hold its 2020 playoffs in empty arenas. This provided an unprecedented opportunity to study how crowds may influence penalties awarded by referees in an ecological context. Using data from playoff games played during the COVID-19 pandemic and the previous 5 years (n = 547), we estimate the number of penalties called by referees depending on whether or not spectators were present. The results show an interaction between a team`s status (home; away) and the presence or absence of crowds. Post-hoc analyses reveal that referees awarded significantly more penalties to the away team compared to the home team when there is a crowd present. However, when there are no spectators, the number of penalties awarded to the away and home teams are not significantly different. In order to generalize these results, we took advantage of the extension of the pandemic and the unusual game setting it provided to observe the behavior of referees during the 2020-2021 regular season. Again, using data from the National Hockey League (n = 1639), but also expanding our sample to include Canadian Hockey League games (n = 1709), we also find that the advantage given to the home team by referees when in front of a crowd fades in the absence of spectators. These findings provide new evidence suggesting that social pressure does have an impact on referees` decision-making, thus contributing to explain the phenomenon of home advantage in professional ice hockey.